Techno-economic evaluation of probioticated Kunu-zaki drinks produce from millet and cocoa powder - Babatunde Olawoye; Ayodeji F. Afolayan; Omotade R. Ogunremi; Isaac O. Olaoye (The Proceedings of the Nigerian Academy of Science)
The increase in the world population has led to the increase in the demand for probioticated yoghurt. However, due to the current economic woes, there has been a need for the production of probioticated yoghurt from alternative sources such as cereals for countries with less comparative advantage in milk production. Owing to this, the work aimed at evaluating the techno-economic analysis of the production of probioticated Kunu-zaki drinks using millet and cocoa powder. The production process was based on the assumption of a uniform cash flow over a period of 10 years. The equipment for the production process was identified based on the process flow chart. The Kunu-zaki production process was based on a constant mass flow of 7500 packets/hr while the sensitivity of the plant was examined by varying the plant operation days. The techno-economic analysis of the plant revealed that the capital cost and annual operation cost were N6.26 ×108and N2.67× 109, respectively. The annual revenue after tax was N6.56 × 108while the return of investment, single payback period, discounted payback period, gross margin and internal rate of return were 64%, 1.56 years, 2.06 years, 23.08 and 78.02%, respectively. The sensitivity analysis of the plant revealed the feasibility of the plant at 330 and 300 operation days.